Outcomes of cataract surgery training among ophthalmology trainees in the independent sector and within the NHS - Darren Shu Jeng Ting; Philip Severn; Qasim Mansoor; Yunzi Chen; Oonagh Crothers (BMJ Open Ophthalmology)
Objective The surge in National Health Service (NHS) cataract procedures in the independent sector (IS) has reduced opportunities for cataract surgical training among ophthalmology trainees. This study aims to analyse IS cataract surgery training outcomes and explore its potential as a supplement to NHS-based training by comparing IS outcomes with NHS and National Ophthalmology Database (NOD) standards.Methods and analysis Two trainees (ST5 and ST3) trained in IS high volume and standard NHS lists. A comprehensive IS training programme included modular cataract training, structured feedback framework and non-technical skills development. Prospective data concerning case numbers, complexity, take-over, outcomes and complication rates were collected and compared.Results In total, 161 IS and 62 NHS cases were analysed. On average, trainees did 6 cases/12 patient lists in IS versus 3 cases/6 patient lists in NHS. IS cases had similar complexity to NHS cases (43% IS vs 35% in NHS, p=0.32, adjusted p=1). Intraoperative complications (3% IS vs 5% NHS, p=0.53, adjusted p=1) and posterior capsule ruptures (1% IS vs 0% NHS, p=0.38, adjusted p=1) were similar, aligning with NOD standards. Based on cases without any ocular comorbidity, the proportion of eyes achieving a good visual outcome (≥6/12 Snellen vision) was similar between IS (100%) and NHS (96%) (p=0.12, adjusted p=1). Surgical efficiency was maintained with all lists completed within 4 hours.Conclusion A structured training programme on high-volume lists within IS setting provided two trainees with valuable exposure to diverse cataract cases while ensuring safety and efficiency, producing training outcomes comparable to the NHS and NOD standards. This is a pilot study, and a much larger multicentre study will be required before the widespread introduction of training in cataract surgery in the IS can be recommended.